LaSEWeb: Automating Search Strategies Over Semi-structured Web Data - Polozov, Oleksandr; Gulwani, Sumit (KDD'14, August 24-27, 2014, New York, NY, USA, 2014)
We show how to programmatically model processes that humans use when extracting answers to queries (e.g., “Who invented typewriter?”, “List of Washington national parks”) from semi-structured Web pages returned by a search engine. This modeling enables various applications including automating repetitive search tasks, and helping search engine developers design micro-segments of factoid questions. We describe the design and implementation of a domain-specific language that enables extracting data from a webpage based on its structure, visual layout, and linguistic patterns. We also describe an algorithm to rank multiple answers extracted from multiple webpages. On 100,000+ queries (across 7 micro-segments) obtained from Bing logs, our system LaSEWeb answered queries with an average recall of 71%. Also, the desired answer(s) were present in top-3 suggestions for 95%+ cases.